Awareness of Industry 4.0 and its tools across the V4 countries, Serbia and Bulgaria - Zauskova, Anna; Kusa, Alena; Kubovics, Michal; Scepkova, Simona; Miklencicova, Renata (Serbian Journal of Management, 2022)
The researched countries, which include the V4 countries, Serbia and Bulgaria, are working to exploit the potential that digitization offers under the Industry 4.0 concept. The rise of Industry 4.0 has resulted in tools such as machine learning, big data, automation, and robotics. In the current environment, we observe it in almost every business entity and across the V4 countries, Serbia and Bulgaria. Awareness of Industry 4.0 continues to grow in the current environment, precisely as a result of the expansion of Industry 4.0. The countries studied are taking Industry 4.0 tools to a new level. To obtain an up-to-date picture of the researched issue, our own questionnaire survey was used, which was used to examine and analyze the current level of Industry 4.0, and the results included in this paper can be compared with the results of the current level of Industry 4.0 in other countries. In order to obtain objective results from the questionnaire survey, five research areas were determined using five hypotheses. The main benefit of the paper lies in the interpretation of the results of the authors' scientific research, which point to the current level and rate of use of Industry 4.0 tools in the defined areas.
Keywords: big data; cloud computing; digitization; IoT; Industry 4.0; Industry 4.0 tools; online marketing